PERANCANGAN PERBAIKAN PELAYANAN RESTORAN RESTO KITA DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Adiba, Fadia Nur; Rohayati, Yati; Amani, Husni (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This research aims to identify weaknesses in restaurant service which are then corrected by designing recommendations for service improvement using Quality Function Deployment. The method in this research uses the Quality Function Deployment method. The Quality Function Deployment method is used through two iterations, namely House of Quality (iteration one) which aims to translate customer needs into technical characteristics by considering the restaurant's capabilities and Part Deployment (iteration two) which aims to identify prioritized critical parts. Service improvements were carried out based on 10 true customer needs obtained from restaurant customers who had dined in. The first iteration produced 15 technical characteristics and the second iteration produced 31 critical parts which were prioritized for improvements to restaurant services. This research can be concluded that there are 15 prioritized technical characteristics and 31 prioritized critical parts. The results of the technical characteristics and critical parts are the basis for making recommendations for improving restaurant services whose targets need to be met in accordance with the decisions of the owner of Resto Kita.